1997
DOI: 10.1093/toxsci/39.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Genotoxic and Cytotoxic Potential of Mainstream Whole Smoke and Smoke Condensate from a Cigarette Containing a Novel Carbon Filter

Abstract: A novel carbon filter has been developed which primarily reduces the amount of certain vapor phase constituents of tobacco smoke with greater efficiency than the charcoal filters of cigarettes currently in the market In vitro indicators of genotoxic and cytotoxic potential were used to compare the cigarette smoke condensate (particulate phase) or whole cigarette smoke (vapor phase and particulate phase) from cigarettes containing the novel carbon filter with smoke condensate or whole smoke from commercial or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
2
21
0
2
Order By: Relevance
“…However, a marked reduction of the cytotoxicity of the vapor phase was noted, rendering it almost impossible to determine an EC 50 value even though a wider dose range was used compared to that used for the cellulose acetate filtered control cigarette. A similar trend was previously reported for the whole MS of a cigarette containing an AC filter with another design, an effect which was associated with the reduction of vapor phase MS constituents (Bombick et al, 1997). Almost half of the cytotoxicity of the MS vapor phase in this assay has recently been attributed to acrolein and, to a lesser degree, to formaldehyde (Tewes et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…However, a marked reduction of the cytotoxicity of the vapor phase was noted, rendering it almost impossible to determine an EC 50 value even though a wider dose range was used compared to that used for the cellulose acetate filtered control cigarette. A similar trend was previously reported for the whole MS of a cigarette containing an AC filter with another design, an effect which was associated with the reduction of vapor phase MS constituents (Bombick et al, 1997). Almost half of the cytotoxicity of the MS vapor phase in this assay has recently been attributed to acrolein and, to a lesser degree, to formaldehyde (Tewes et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Using this assay we demonstrated that 89% of the observed cytotoxicity of WS is derived from the VP and confirms previous results utilising WS in acute exposure models (Bombick et al, 1997;Saladino et al, 1985;Fukano et al, 2004;). WS exposure also induced an increase in the secretion of all three inflammatory mediators at all smoke doses which is in line with previous observations made with this and other cell culture systems (Phillips et al, 2005;Beisswenger et al, 2004).…”
Section: Inflammatory Mediator Exposure Group Seeding Density and Passupporting
confidence: 90%
“…However, this fraction is devoid of the gas-vapor phase constituents such as acrolein and other reactive compounds (Johnson et al, 2009). Assessment of genotoxic and cytotoxic effects of exposure to whole smoke ideally is achieved by exposing cells directly to freshly generated smoke (Bombick et al, 1997). A commonly employed method to expose cells to whole smoke involves bubbling fresh smoke through aqueous media and using it as the whole smoke aqueous extract (Fukano et al, 2004;Phipps et al, 2010).…”
Section: Introductionmentioning
confidence: 99%